2019
DOI: 10.1002/path.5355
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the roles of ASPM isoforms reveals a novel prognostic marker for pancreatic cancer

Abstract: † Invited commentary for Hsu et al. The differential distributions of ASPM isoforms and their roles in Wnt signaling, cell cycle progression, and pancreatic cancer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Whilst the preceding data support the importance of ASPM in GC, they did not distinguish among different protein isoforms of ASPM, which may play different roles in oncogenesis [20,36]. To this end, we carried out TMA analysis of 59 GC tissues and the paired normal gastric epithelium for the staining of ASPMiI and ASPMiII using isoform-specific antibodies recently developed by our group.…”
Section: The Expression Of Aspmii Is Prognostically Important In Gcmentioning
confidence: 96%
“…Whilst the preceding data support the importance of ASPM in GC, they did not distinguish among different protein isoforms of ASPM, which may play different roles in oncogenesis [20,36]. To this end, we carried out TMA analysis of 59 GC tissues and the paired normal gastric epithelium for the staining of ASPMiI and ASPMiII using isoform-specific antibodies recently developed by our group.…”
Section: The Expression Of Aspmii Is Prognostically Important In Gcmentioning
confidence: 96%
“…Previous studies have shown that ASPM is highly expressed in a variety of cancers and is related to a poor clinical prognosis and recurrence ( 37 ). Accumulating evidence suggests that ASPM is a regulator of cell stemness, it enhances stem cell phenotype in prostate cancer cells by enhancing Wnt/β-catenin signaling, thereby promoting tumor aggressiveness ( 38 ). ASPM acts as an immune-related gene in bladder cancer ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…An improper response to DNA damage is a cancer hallmark and contributes to tumorigenesis and chemo/radiotherapeutic resistance. ASPM overexpression has been observed in various cancers ( Xu et al., 2019 , 2020 ; Zhou et al., 2020 ; Alsiary et al., 2014 ; Bruning-Richardson et al., 2011 ; Saleh et al., 2020 ; Xie et al., 2017 ; Tian and Wang, 2020 ; Timaner and Shaked, 2020 ; Hsu et al., 2019 ; Wang et al., 2013 ; Tang et al., 2019 ; Lin et al., 2008 ; Yuan et al., 2020 ; Wu et al., 2021 ) and thus might serve as a prognostic marker in various contexts. ASPM is a positive regulator of the canonical Wnt/β-catenin signaling ( Major et al., 2008 ; Hsu et al., 2019 ) and thus promotes cancer stemness and progression in prostate cancer ( Pai et al., 2019 ) and hepatocellular carcinoma ( Liao et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%